BRAC’s (ব্র্যাক) Adoption of Community-Based Primary Education for Socially Disadvantaged Children in Bangladesh - Mohammad Abul Fateh (Cadernos de História da Educação)
This article provides a critical-historical analysis of BRAC’s adoption of non-formal primary education (NFPE) while de-emphasizing ‘conscientizing’ functional education in Bangladesh during 1980s. The central question of this paper is why did BRAC´s adopt NFPE in 1985 within the framework of its needs. In this study, I analyze BRAC’s education program from 1973 to 1985, with particular attention to the international neoliberal context of 1980s, policy shift of the western aid industry, and relationship that BRAC and its founder had with local power structures and consecutive Bangladeshi regimes (Fateh, 2020). I examine BRAC’s curriculum documents, project proposals, evaluation reports, and statements made by BRAC’s founder Fazle Hasan Abed. My findings suggest that beside supporting the disadvantaged children, BRAC’s adoption of NFPE is for the sake of its organizational growth associated to its submission to local power structure, and dominant neoliberal framework of the international aid industry.